2018
DOI: 10.3390/ijms19113625
|View full text |Cite
|
Sign up to set email alerts
|

Development of Pectin-Type B Gelatin Polyelectrolyte Complex for Curcumin Delivery in Anticancer Therapy

Abstract: Curcumin has been proven to be a potent agent in colon cancer treatment. However, its hydrophobicity and low oral bioavailability hampered its clinical application. These limitations could be improved through appropriate formulations such as using polyelectrolyte complexes (PECs). PECs were self-assembled with polycations and polyanions in polar solvents. In this study, a novel pectin-type B gelatin PEC was developed for use in curcumin formulation. At pH 4.0, natural polyanions pectin and polycations type B g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 39 publications
(50 reference statements)
0
4
0
Order By: Relevance
“…Pectin maintains curcumin’s integrity and bioactivity and delivers it to the target site in the colon cancer cell. Pectin-type B gelatin curcumin conjugates have been more effective for curcumin delivery through oral administration in anti-cancer agents [ 100 ]. Pectin and curcumin were conjugated via the esterification reaction between carboxylic groups of pectin and phenolic –OH group of curcumin ( Figure 5 ).…”
Section: Polysaccharides Based Drug Carriersmentioning
confidence: 99%
“…Pectin maintains curcumin’s integrity and bioactivity and delivers it to the target site in the colon cancer cell. Pectin-type B gelatin curcumin conjugates have been more effective for curcumin delivery through oral administration in anti-cancer agents [ 100 ]. Pectin and curcumin were conjugated via the esterification reaction between carboxylic groups of pectin and phenolic –OH group of curcumin ( Figure 5 ).…”
Section: Polysaccharides Based Drug Carriersmentioning
confidence: 99%
“…It is used for a better description of drug release behavior from a polymeric system as shown in equation 4Log (Q t /Q ∞ ) = log K kp + n log t ……… (4) Where Q t /Q ∞ = the fraction of drug release at time t, Kkp =the constant incorporating structural and geometrical features of controlled release device and (n) = a diffusional release exponent indicative of the drug release mechanism for dissolution.…”
Section: Korsmeyer-peppas Modelmentioning
confidence: 99%
“…Besides, curcumin in a buffer decomposes in a pH-dependent manner, and this degradation accelerates at neutral-basic conditions. Studies have suggested that curcumin could be well formulated to improve its solubility and bioavailability via a reliable controlled-or sustained-release system 4,5 .…”
mentioning
confidence: 99%
“…Gelatin is a biodegradable polymer that has a protein content of 85-92%. This material is non-toxic, does not induce immunological reactions, and is generally suitable for cell adhesion and viability [11,12]. Gelatin, due to its versatile applicability, has been used for over a millennium in the food, cosmetic, and pharmaceutical industries.…”
Section: Introductionmentioning
confidence: 99%